2005
DOI: 10.1042/bj20040887
|View full text |Cite
|
Sign up to set email alerts
|

Specific interactions of PP2A and PP2A-like phosphatases with the yeast PTPA homologues, Ypa1 and Ypa2

Abstract: To elucidate the specific biological role of the yeast homologues of PTPA (phosphatase 2A phosphatase activator), Ypa1 and Ypa2 (where Ypa stands for yeast phosphatase activator), in the regulation of PP2A (protein phosphatase 2A), we investigated the physical interaction of both Ypa proteins with the catalytic subunit of the different yeast PP2A-like phosphatases. Ypa1 interacts specifically with Pph3, Sit4 and Ppg1, whereas Ypa2 binds to Pph21 and Pph22. The Ypa1 and Ypa2 proteins do not compete with Tap42 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…This insertion appears feasible from a structural perspective and could possibly be involved in changing the protein-protein interaction pattern of PTPA. The yeast PTPA homologs Rrd1 and Rrd2 interact with the conserved Tap42 protein (␣4 in humans) and with the type 2A phosphatases (16,17). Tap42 also interacts with type 2A phosphatases, and this complex is a crucial part in mediating the signal through the TOR pathway, a nutrient-responsive signaling pathway (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This insertion appears feasible from a structural perspective and could possibly be involved in changing the protein-protein interaction pattern of PTPA. The yeast PTPA homologs Rrd1 and Rrd2 interact with the conserved Tap42 protein (␣4 in humans) and with the type 2A phosphatases (16,17). Tap42 also interacts with type 2A phosphatases, and this complex is a crucial part in mediating the signal through the TOR pathway, a nutrient-responsive signaling pathway (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…PTPA is an essential protein as revealed by its high evolutionary conservation as well as the lethality of the deletion of the two PTPA homologs in yeast, Rrd1 and Rrd2, in certain nutritional backgrounds (15). Rrd1/2 also interact with other less abundant type 2A phosphatases (16,17). Interestingly, the effect of deleting Rrd1/2 is more severe than deletion of the yeast PP2Ac, most likely due to the fact that the different type 2A phosphatases in yeast can partly take over each others roles (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rrd2p binds directly to the PP2A catalytic subunits Pph21p and Pph22p, and is more potent in the activation of PP2A catalytic subunits than Rrd1p. It has also been suggested that Rrd1p and Rrd2p may cooperate in the activation of PP2A (Van Hoof et al 2005). Rrd1p also activates the PP2A-related phosphatase Sit4p (Douville et al 2004;Mitchell and Sprague 2001).…”
Section: S Pombe Ptpa Genesmentioning
confidence: 99%
“…TIP41 dephosphorylation correlates with an increased association of TIP41 with TAP42, but here too, the physiological relevance of TIP41 phosphorylation in this process has not been confirmed (Jacinto et al, 2001). Presumably, the phosphorylation status of TAP42 and/or its association with TIP41 alters the substrate specificity of associated phosphatases (Du¨vel et al, 2003;Du¨vel and Broach, 2004;Van Hoof et al, 2005;Zheng and Jiang, 2005). The latest model (Yan et al, 2006) posits that TORC1 regulates TAP42-associated phosphatases via direct physical interaction, which sequesters the phosphatases with TORC1 at membranes.…”
Section: Torc1 Regulated Protein Phosphatasesmentioning
confidence: 99%